Archaeology of wings : Birds and people in the Baltic Sea region during the Stone Age - Mannermaa, Kristiina (Helsingin yliopisto, 2010)
The prominent roles of birds, often mentioned in historical sources, are not well reflected in archaeological research. Absence or scarcity of bird bones in archaeological assemblages has been often seen as indication of a minor role of birds in the prehistoric economy or ideology, or explained by taphonomic loss. Few studies exist where birds form the basis for extensive archaeological interpretation. In this doctoral dissertation bird bone material from various Stone Age sites in the Baltic Sea region is investigated. The study period is approximately 7000-3400 BP, comprising mainly Neolithic cultures. The settlement material comes from Finland, Åland, Gotland, Saaremaa and Hiiumaa. Osteological materials are used for studying the economic and cultural importance of birds, fowling methods and principal fowling seasons. The bones were identified and earlier identifications partially checked with help of a reference material of modern skeletons. Fracture analysis was used in order to study the deposition history of bones at Ajvide settlement site. Birds in burials at two large cemeteries, Ajvide on Gotland and Zvejnieki in northern Latvia were investigated in order to study the roles of birds in burial practices. My study reveals that the economic importance of birds is at least seasonally often more prominent than usually thought, and varies greatly in different areas. Fowling has been most important in coastal areas, and especially during the breeding season. Waterbirds and grouse species were generally the most important groups in Finnish Stone Age economy. The identified species composition shows much resemblance to contemporary hunting with species such as the mallard and capercaillie commonly found. Burial materials and additional archaeological evidence from Gotland, Latvia and some other parts of northern Europe indicate that birds –e.g., jay, whooper swan, ducks – have been socially and ideologically important for the studied groups (indicating a place in the belief system, e.g. clan totemism). The ...